2020
DOI: 10.3389/fams.2019.00066
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Pass-Through Investigation for Turkish Economy

Abstract: Turkish economy continued to rapidly open up in the last 40 years. It has long been in the top 20 largest economies in the world. Exchange rate is an important variable affecting micro and macro variables in the economy. This study aims to investigate the effect of exchange rate changes on the producer and consumer prices in Turkey by using the VAR model. Results show the degree of transition with effect-response functions and how the prices were affected by variance decomposition by using the 2005-2019 monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The estimated results revealed that ERPT in Egypt is incomplete and slow in three price indices of Import Price Index, Producer Price Index and Consumer Price Index. Kotil (2020) examined the ERPT for the Turkish economy and found that the effect of change in exchange rate is higher for the Producer Price Index than the Consumer Price Index.…”
Section: A Review Of Literature On Empirical and Recent Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated results revealed that ERPT in Egypt is incomplete and slow in three price indices of Import Price Index, Producer Price Index and Consumer Price Index. Kotil (2020) examined the ERPT for the Turkish economy and found that the effect of change in exchange rate is higher for the Producer Price Index than the Consumer Price Index.…”
Section: A Review Of Literature On Empirical and Recent Studiesmentioning
confidence: 99%
“…According to the Kotil (2020), Exchange Rate Pass-Through is complete when most of the exchange rate movement is transferred to domestic prices. If the degree of passthrough is high, then the then the relative changes of the prices of imports in the domestic currency is high casing pay higher price for imports goods due to the higher fluctuations in the Nominal Exchange Rate (NER).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there had not been a general consensus on the interaction effect between exchange rate and inflation. Kotil (2020) noted that there had been an increased in empirical studies on ERPT in both developed and emerging economies, and the literature had focused on two approaches. According to the author, the first approach is on factors affecting the transition effect, while the second approach focuses on pass-through duration and its magnitude.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, recent empirical studies on the exchange rate -inflation nexus were evaluated and yet no general consensus on the interaction effect between exchange rate and inflation was evident. Among the studies include, Kotil (2020) who examined ERPT to domestic prices in Turkey covering the period of 2005 to 2019. Utilizing the VAR model procedure, the results indicate a greater response to consumer prices than the producer prices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation